Healthcare related factors associated with mono-infection and co-infection of bloodborne viruses in Lasbela and Quetta, Baluchistan - Rasheed, Nida; Karim , Mehtab; Ali, Syeda Tabeena (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the frequency of human immunodeficiency virus, hepatitis B virus and hepatitis C virus infection, and to compare the prevalence and risk factors of mono-infection versus co-infection. Method: The comparative, cross-sectional study was conducted in selected hospitals in Lasbela and Quetta districts of Balochistan, Pakistan, from November 2022 to April 2023, and comprised patients of either gender aged >18 years visiting the participating hospitals. The patients were screened using an immunochromatographic test kit, and were divided into mono-infected with human immunodeficiency virus group 1, mono-infected with hepatitis C virus group 2, mono-infected with hepatitis B virus group 3, co-infected with two or three viruses group 4, and healthy controls group 5. Factors associated with co-infection versus mono-infection of blood-borne viruses were identified. Data was analysed using SPSS 21. Results: Of the 1992 subjects, 1043(52.4%) were females, 949(47.60%) were males, and 864(43.4%) were aged 30-44 years. Of the total, 75(3.8%) subjects were in group 1, 175(8.8%) in group 2, 88(4.4%) in group 3, 79(4%) in group 4, and 1,575(79.1%) in control group 5. In group 4, 27(34.1%) subjects had human immunodeficiency virus and hepatitis B virus, followed by 26(32.9%) having hepatitis B virus and hepatitis C virus, 17(21.5%) having human immunodeficiency virus and hepatitis C virus, and 9(11.3%) having triple infection. Among other findings, history of surgical procedures, male gender and rural residence were significantly associated with co-infection (p<0.05). Conclusion: Strengthening infection control practices in district hospitals, expanding vaccination coverage, incorporating supplementary testing methods, and promoting community awareness campaigns about safe injection and transfusion practices are to control the risk of life-threatening virus in the community. Key Words: Hepatitis C, Hepatitis B, Mono-infections, Co-infection, Prevalence, Balochistan.